ANALISIS KARAKTERISTIK, PEMASARAN LANGSUNG, DAN WORD OF MOUTH TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH DI SULAWESI SELATAN - ST. Rukaiyah (Jurnal Bisnis dan Kewirausahaan, 2017)
The result of the calculation using the software SPSS version 17.0 Fhitung result 10 277 . In Table Model Summary (b) is known by 3 DF1 and DF2 of 96. With α level of 5% , then it can be known Ftabel of 2.33. Therefore Fhitung greater than Ftable (10 277 > 2.33) , then Ho is rejected . This implies that the independent variable ( X1-3 ) jointly have a significant effect on the dependent variable (Y) . In other words that characteristic , direct marketing , and word of mouth are analyzed simultaneously have a significant influence on the improvement of the performance of SMEs . The coefficient of determination Adjusted R Square of 0.571 means that 57.10 % of variation of the variable performance of micro, small and medium enterprises (SMEs ) can be explained by the characteristic variable (X1), direct marketing (X2) , and word of mouth (X3). While 57.10 % is explained by other variables not included in the model